2018
DOI: 10.3928/01484834-20180322-05
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Peer Mentorship as an Educational Strategy in Nursing

Abstract: Peer mentorship as a valuable educational strategy can be recognized for future use within all levels of nursing education and can be applied universally to teaching and learning within other health care educational settings. [J Nurs Educ. 2018;57(4):217-224.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 11 publications
1
54
0
4
Order By: Relevance
“…Traditionally, tutors or mentors are supposed to be more experienced than mentees in mentorship (Grossman, 2012). Also, Andersen and Watkins (2018) stated that the mentor is often an experienced nursing student within the program who has overcome the trials a new nursing student experiences to increase Walker et al(2016) 0.462 0.232 0.008 0.916 0.046 Brannagan et al(2013) 0.311 0.075 0.164 0.458 0.000 Ha et al(2018) -0.232 0.105 -0.437 -0.027 0.027 Iwasiw et al(1993) 0.257 0.140 -0.018 0.532 0.067 Badowski et al(2017) 0.796 0.175 0.453 1.139 0.000 Kim et al(2018) 0.663 0.174 0.322 1.005 0.000 Lakdizaji et al(2013) 0 Figure 2 Forest plots for primary studies. the benefits of peer learning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditionally, tutors or mentors are supposed to be more experienced than mentees in mentorship (Grossman, 2012). Also, Andersen and Watkins (2018) stated that the mentor is often an experienced nursing student within the program who has overcome the trials a new nursing student experiences to increase Walker et al(2016) 0.462 0.232 0.008 0.916 0.046 Brannagan et al(2013) 0.311 0.075 0.164 0.458 0.000 Ha et al(2018) -0.232 0.105 -0.437 -0.027 0.027 Iwasiw et al(1993) 0.257 0.140 -0.018 0.532 0.067 Badowski et al(2017) 0.796 0.175 0.453 1.139 0.000 Kim et al(2018) 0.663 0.174 0.322 1.005 0.000 Lakdizaji et al(2013) 0 Figure 2 Forest plots for primary studies. the benefits of peer learning.…”
Section: Discussionmentioning
confidence: 99%
“…As peer learning has been known by various names, four combined search terms were used: ''peer instruction'' OR ''peer-assisted learning'' OR ''peer learning'' OR ''peer tutoring'' AND ''nursing student'' OR ''nursing undergraduate.'' Lastly, screening of the bibliographies of review articles (Allan et al, 2008;Andersen & Watkins, 2018;Andrews & Manning, 2016;Boud, 2001;Crouch & Mazur, 2001;Crouch et al, 2007;Dennison, 2010;Green, 2001;Grossman, 2012;Lasry et al, 2008;Roberts, 2008;Stone et al, 2013) was also performed with the aim of identifying studies, which were not discovered with the electronic search. The references of all the review articles were checked manually for relevant articles, which are not indexed searching in the databases by the researcher (JH).…”
Section: Data Sources and Searchesmentioning
confidence: 99%
See 2 more Smart Citations
“…Holst and Hörberg () found that peer learning created a sense of belongingness that facilitated independence and professional development. Additionally, findings from recent studies by Pålsson, Mårtensson, Leo Swenne, Ädel, and Engström () and Andersen and Watkins () indicate that peer learning facilitates an increased understanding of collaboration and leadership. Despite these positive benefits, there have also been reports of negative outcomes, such as competition among students (Stenberg & Carlson, ) and students not feeling safe or compatible with each other (Holst & Hörberg, ), that are seen to have an impact on student learning.…”
Section: Introductionmentioning
confidence: 99%